Creep Deformation of a Cu-Zr Nanoglass and Interface Reinforced Nanoglass-Composite Studied by Molecular Dynamics Simulations - Kalcher, Constanze; Adjaoud, Omar; Albe, Karsten (Frontiers in Materials, 2020)
By means of molecular dynamics simulations we compare the creep properties of a homogeneous Cu64 Zr36 metallic glass, a nanoglass with the same nominal composition, and a nanoglass-crystal composite, where the amorphous grain boundary phase has been reinforced with the high-temperature stable Cu2Zr Laves phase. While the nanoglass architecture is successful at preventing shear band formation which typically results in a brittle failure mode at room temperature and conventional loading conditions, we find that the high fraction of glass-glass grain boundary phase therein is not beneficial to its creep properties. This can be amended by reinforcing the glass-glass interphase with a high-temperature stable crystalline substitute.